2020
DOI: 10.1109/tuffc.2020.2976809
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study on Convolutional Neural Networks for Motion Estimation From Ultrasound Images

Abstract: In recent years, deep learning has been successfully applied to the analysis and processing of ultrasound images. To date, most of this research has focused on segmentation and view recognition. This paper benchmarks different convolutional neural network algorithms for motion estimation in ultrasound imaging. We evaluated and compared several networks derived from FlowNet2, one of the most efficient architectures in computer vision. The networks were tested with and without transfer learning and the best conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 22 publications
(33 reference statements)
1
13
0
Order By: Relevance
“…In a recent pilot study, efforts were also made into benchmarking different networks components of FlowNet 2.0, with fine-tuning on simulated US data. The results were on par with current state of the art for flow estimation [17]. In sum, these studies indicate a potential and adaptability for CNN based ME in US image analysis.…”
Section: Introductionsupporting
confidence: 60%
“…In a recent pilot study, efforts were also made into benchmarking different networks components of FlowNet 2.0, with fine-tuning on simulated US data. The results were on par with current state of the art for flow estimation [17]. In sum, these studies indicate a potential and adaptability for CNN based ME in US image analysis.…”
Section: Introductionsupporting
confidence: 60%
“…By definition, these techniques are optimal to the data they are trained on. Such approaches have been applied in the context of left ventricular structures analysis [10], [11], in particular for segmentation. In 2012, Carneiro et al exploited deep belief networks and the decoupling of rigid and nonrigid classifiers to improve robustness in terms of image conditions and shape variability [12].…”
Section: A Related Workmentioning
confidence: 99%
“…In this context, ultrasound simulations can play a key role in building such datasets. In this regard, our recent pilot study has shown that DL techniques can learn from synthetic ultrasound sequences to improve a targeted task; in this case, the estimation of rotational movements on in vitro data [12].…”
Section: Introductionmentioning
confidence: 99%